"House Arrest" or "Developmental Arrest"? A Study of Youth Under House Arrest. (October 2018) - Chamiel, Elad; Walsh, Sophie D.
Studies have examined the potential benefits and risks of alternative forms of detention, such as house arrest, for adults but, despite its growing use, little research has examined the implications of house arrest for juveniles. The current research examined the experience of 14 adolescents under house arrest. Six main themes were identified in the narratives of the participants: the experience of detention, daily schedule and utilization of time, emotions and self-reflection, relationships with peers, relation to parents and supervisor(s), and contact with professionals. Findings emphasized the potential developmental dangers of house arrest at the critical stage of adolescence. Yet, analysis also showed that the period of house arrest has the potential to be a period of positive changes, and can be used for successful rehabilitation.